2020
DOI: 10.1101/2020.12.03.393306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple viral microRNAs regulate interferon release and signaling early during infection with Epstein-Barr virus

Abstract: Epstein-Barr virus (EBV), a human herpes virus, encodes 44 microRNAs (miRNAs), which regulate many genes with various functions in EBV-infected cells. Multiple target genes of the EBV miRNAs have been identified, some of which play important roles in adaptive antiviral immune responses. Using EBV mutant derivatives, we identified additional roles of viral miRNAs in governing versatile type I interferon (IFN) responses upon infection of human primary mature B cells. We also found that Epstein-Barr virus-encoded… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…v-miRNAs are emerging post-transcriptional regulators of host immune responses and have been ascribed immunoevasive functions [reviewed in (Cullen, 2013)]. For example, v-miRNAs produced by other dsDNA viruses (EBV, hCMV, KSHV) have been found to target host antiviral genes resulting in repression of proinflammatory cytokine production and release (Abend et al, 2012; Abend et al, 2010; Bouvet et al, 2021; Hancock et al, 2017; Hook et al, 2014; Landais et al, 2015; Lau et al, 2016; Lei et al, 2010). Accordingly, target prediction and pathway analyses revealed that FV3 v-miRNAs are predicted to target host genes involved in several antiviral pathways such as the cGAS-STING, RIG-I/MDA5, TLR3, TLR4, TLR9, and type I IFN signaling pathways, as well as the downstream products of signaling pathways triggered by virus sensing by these PRRs (NF-κB-induced genes and ISGs), and the impacts of these potential interactions are discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…v-miRNAs are emerging post-transcriptional regulators of host immune responses and have been ascribed immunoevasive functions [reviewed in (Cullen, 2013)]. For example, v-miRNAs produced by other dsDNA viruses (EBV, hCMV, KSHV) have been found to target host antiviral genes resulting in repression of proinflammatory cytokine production and release (Abend et al, 2012; Abend et al, 2010; Bouvet et al, 2021; Hancock et al, 2017; Hook et al, 2014; Landais et al, 2015; Lau et al, 2016; Lei et al, 2010). Accordingly, target prediction and pathway analyses revealed that FV3 v-miRNAs are predicted to target host genes involved in several antiviral pathways such as the cGAS-STING, RIG-I/MDA5, TLR3, TLR4, TLR9, and type I IFN signaling pathways, as well as the downstream products of signaling pathways triggered by virus sensing by these PRRs (NF-κB-induced genes and ISGs), and the impacts of these potential interactions are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that FV3 has evolved the ability to simultaneously impact at least five different antiviral signaling pathways that defend against viruses at the cell membrane, in the cytoplasm, and in the endosome. As impairment of type I IFN signaling has been observed in other viruses such as EBV, hCMV, and KSHV (Abend et al, 2012; Bouvet et al, 2021; Hooykaas et al, 2017; Huang and Lin, 2014; Huang et al, 2015), it will be important to functionally characterize fv3-miR-8-3p, fv3-miR-7-5p, fv3-miR-27-5p, and fv3-miR-28-5p which target mediators of type I IFN signaling. It is also interesting to note that FV3 v-miRNAs appear to mostly target the RIG-I/MDA5 cytoplasmic sensing pathway by specifically targeting genes involved in ubiquitination ( trim25, usp4, usp38 , and trim11 ), suggesting that FV3 may largely regulate this pathway by modulating ubiquitination.…”
Section: Discussionmentioning
confidence: 99%